Evaluation of thermal aging of δ-ferrite in austenitic stainless steel weld using nanopillar compression test. (October 2018) - Lee, Ho Jung; Kong, Byeong Seo; Obulan Subramanian, Gokul; Heo, Jaewon; Jang, Changheui; Lee, Kyoung-Soo
Abstract: The effects of thermal aging on microstructure and mechanical property change of δ-ferrite in an austenitic stainless steel weld were investigated. After thermal aging at 400 °C for 20, 000 h, spinodal decomposition and G phase precipitation were observed, along with 80% increase in yield strength measured by nanopillar compression test. Subsequent reversion heat treatment removed spinodal decomposition while leaving G phase, resulting in partial recovery of hardening in δ-ferrite. It was estimated that 60% of the hardening in the δ-ferrite of the aged specimen was attributed to spinodal decomposition and 40% to G phase, respectively. Graphical abstract: Unlabelled Image